Uji Aktivitas Antioksidan Ekstrak Etanol Daun Salam (Syzygium Polyanthum (Wight) Walp.) Dengan Metode DPPH - Wilson Kanggaran; Razoki, Razoki; Roy Indrianto Bangar Siagian; Hariyadi Dharmawan Syahputra (CV. ITTC INDONESIA, 2025)
Bay leaf (Syzygium polyanthum (Wight) Walp.) is known to contain phenolic and flavonoid compounds with potential as natural antioxidants. This study aims to evaluate the antioxidant activity of ethanol extract of bay leaves using the DPPH method and to identify the bioactive compounds through phytochemical screening and simplicia characterization. Extraction was conducted using maceration with 80% ethanol as the solvent. Characterization result showed that the bay leaf simplicial met the standards of the Farmakope Herbal Indonesia. Phytochemical screening revealed positive results for alkaloids, flavonoids, saponins, tannins, and phenols. The antioxidant activity test showed that the ethanol extract of bay leaves had an IC50 value of 15,45 ppm, which falls into the very strong antioxidant category. These findings reinforce the potential of bay leaf as a natural antioxidant source that can be further developed in pharmaceutical and health applications.